2020
DOI: 10.5398/tasj.2020.43.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Methane Emissions and Rumen Fermentation Profile Treated by Dietary Chitosan: A Meta-Analysis of In Vitro Experiments

Abstract: Chitosan is a natural compound obtained from deacetylation of chitin, which is a biopolymer present in the exoskeleton of crustaceans such as crabs and shrimp. The present study aimed to perform a meta-analysis from published studies regarding the effects of chitosan on methane emission and rumen fermentation profile of in vitro batch culture experiments. A total of 41 studies from 12 articles were integrated into a database. Parameters included were gas production, methane emission, rumen fermentation charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 36 publications
(62 reference statements)
3
16
0
Order By: Relevance
“…As regards CHI, previous studies reported a reduction of gas production using chitin and chitosan and a decrease in the digestibilities of organic matter and dry matter of the ration; the latter was probably due to its antiprotozoal effect [40]. In a meta-analysis, in vitro gas production showed that an increase in the doses of chitosan was associated with a decrease in total gas production (p < 0.001), reduction of the protozoa population (p < 0.05), and an increase of the total microbial population (p < 0.01) [43].…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…As regards CHI, previous studies reported a reduction of gas production using chitin and chitosan and a decrease in the digestibilities of organic matter and dry matter of the ration; the latter was probably due to its antiprotozoal effect [40]. In a meta-analysis, in vitro gas production showed that an increase in the doses of chitosan was associated with a decrease in total gas production (p < 0.001), reduction of the protozoa population (p < 0.05), and an increase of the total microbial population (p < 0.01) [43].…”
Section: In Vitro Experimentsmentioning
confidence: 99%
“…There is also a toxic effect of tannins on rumen microbes in the terminal stage of BH, which has a positive impact on increasing the percentage of rumen intermediate fatty acids [56]. Similarly, a meta-analysis of 12 articles on natural rumen biomodifiers, for example chitosan, showed similar characteristics to tannin supplementation, such as reduced SFA, and increased rumen CLA and PUFA with in vitro batch culture [57].…”
Section: Discussionmentioning
confidence: 93%
“…The increase of nutrient digestibility of ruminants due to chitin and chitosan is seemed to be related to the change of microbial population structure in the rumen. The compounds decrease the population and activity of protozoa, and subsequently decrease predation of the fauna on rumen bacteria, and finally enhance the bacteria population for degrading substrates (Harahap et al, 2020). Further, the compounds may act like tannins that elevate protein utilisation in the digestive tracts of ruminants (Kondo et al, 2014;Jayanegara et al, 2019).…”
Section: Resultsmentioning
confidence: 99%